Dissenting opinion: The voice of the future - Ali Mohamed, Ashgar Ali (LexisNexis, 2016)
This article deals with the legal point of view of the dissenting opinion with reference to the recent Federal Court's split 3-2 ruling in Majlis Agama Islam Wilayah Persekutuan & Anor v Victoria Jayaseele Martin. The dissenting opinion which had subsequently changed the legal doctrine or position is discussed with reference to the New Zealand Court of Appeal's decision in Brighouse Ltd v Bilderbeck. The minority decision in Brighouse Ltd's case was followed in Aoraki Corporation Ltd v McGavin, a decision of the Court of Appeal comprising a panel of seven judges.